HUBUNGAN ASUPAN LEMAK, ASUPAN SERAT, DAN PENGETAHUAN DALAM PEMILIHAN MAKANAN DENGAN KEJADIAN GIZI LEBIH PADA REMAJA - Fadhilah Rahmah (2023)
Overnutrition is a condition that occurs in a person when the energy entering the body is more than the energy expended by the body. Adolescents are one of the age groups at risk of being overweight. This study aims to determine the relationship between fat intake, fiber intake, and food selection knowledge with the incidence of overnutrition in adolescents. Observational study with a cross-sectional design was conducted in Tapos Sub-district, Depok City. The study included 65 students aged 16-19 years, selected using the Incidental Sampling technique. The study used anthropometric data, knowledge questionnaire instrument on food selection, and SQ-FFQ (Semi Quantitative-Food Frequency Questionnaire) questionnaire. Data analysis was performed with the Chi-square test. The results showed that the nutritional status of adolescents ranged from 70.8% normal nutritional status to 29.2% overnutrition status. The results of Statistic test showed that there was relationship of fat intake (p = 0.000) and food selection knowledge (p = 0.004) with the incidence of overnutrition, but there was no relationship between the incidence of overnutrition with fiber intake (p = 0.974). Conclusion of the result: There was a relationship between fat intake and food selection knowledge with incidence of overnutrition, but there was no relationship between fiber intake with the incidence of overnutrition.